Concentric Needle Jitter Measurements in Voluntarily Activated Deltoid Muscle in Healthy Control Subjects - Kouyoumdjian, João Aris; Graca, Carla Renata (Muscle & nerve, 2025)
ABSTRACT Introduction/Aims The deltoid muscle demonstrates sensitivity in detecting abnormal decrement on repetitive nerve stimulation in cases of myasthenia gravis and congenital myasthenic syndromes. However, single‐fiber electromyography (concentric needle jitter) normative data is currently lacking, which this study aims to address. Methods Jitter, measured by the mean consecutive difference (MCD), was assessed in the voluntarily activated deltoid muscle of 32 healthy adults (16 men and 16 women) with no known or suspected neuromuscular disease. For each subject, the mean MCD of 20 pairs was calculated. The overall jitter reference value was the mean MCD across all subjects, while the 18th highest MCD among them defined the individual jitter reference value (outliers). Results The average age of the male subjects was 42 years (ranging from 21 to 61), while the average age for females was 46 years (ranging from 32 to 65). The mean MCD values were 21.15 ± 3.42 μs for men and 19.50 ± 2.34 μs for women. For individual assessments, the 18th highest MCD was recorded as 27.84 ± 4.68 μs for men and 25.42 ± 3.19 μs for women. Discussion The proposed reference values for normal mean MCD are < 28 μs for men and < 26 μs for women. The normal outlier limits are < 38 μs for men and < 32 μs for women. No previously reported values for the deltoid muscle are available for comparison.